Penegakan Hukum Tindak Pidana Korupsi di Indonesia: Tantangan, Hambatan, dan Solusi - Ni Putu Sri Widiasih (Indo Publishing, 2026)
Law enforcement against corruption crimes in Indonesia has experienced significant development since the reform era through the strengthening of legal frameworks and law enforcement institutions, particularly the Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK), as well as the enactment of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption Crimes as a lex specialis outside the Criminal Code. Nevertheless, the effectiveness of corruption law enforcement continues to face various challenges, including weak inter-institutional coordination, political intervention, a high level of social tolerance toward corrupt practices, and the increasing complexity of corruption cases involving money laundering schemes. Additional obstacles include regulatory inconsistencies, limited asset recovery outcomes, and constraints in institutional capacity. Therefore, strategic solutions are required, such as regulatory reform aligned with international standards, particularly the United Nations Convention against Corruption (UNCAC), strengthening the capacity and independence of law enforcement agencies, enhancing transparency and accountability, and increasing public participation in corruption prevention and oversight. This study provides a comprehensive analysis of the development of corruption law enforcement in Indonesia and offers policy recommendations to strengthen future anti-corruption efforts.